Rancang Bangun dan Kalibrasi Dinamometer Silinder Berlubang untuk Proses Gurdi - Aulia, A; Triyono; Soeharsono (Jurnal MESIL (Mesin Elektro Sipil), 2025)
The drilling process is a machining operation that involves cutting a workpiece using a two-edged cutting tool. During this process, cutting forces are generated. A device used to measure these forces is called a dynamometer. This final project focuses on the design of a table-type dynamometer for drilling operations. The dynamometer consists of strain gauges mounted on the sides of a hollow cylindrical load cell and a pointer for digital output indication. The load cell was designed using the CAD/CAM software CATIA V5, and its dimensions were determined by analyzing the strength of the hollow cylinder using the Ansys application. Once the design was analyzed, the dynamometer was fabricated. Prior to use, the dynamometer was calibrated using static loading. The calibration data analysis was based of the relationship between the strain gauge output and the applied static force. The dynamometer is expected to measure both compressive force and torque. Calibration results showed that static loads ranging from 100 N to 500 N and torque from 5 Nmm to 30 Nmm demonstrated a linear relationship between the applied load and the dynamometer output, each with a gradient that indicates a strong functional correlation.